Policy creation and evaluation understanding welfare reform in the United States - Hoefer, Richard (New York ; Oxford : Oxford University Press, 2011)
This pocket guide will be useful to researchers as well as students in advanced social policy courses seeking to understand the two stages of policy-making, to develop policy, to be able to describe the impact of social policy on social problems.
Also issued in print format.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public welfare -- United States; Public welfare -- Law and legislation -- United States; United States -- Social policy